PENGARUH LATIHAN PLYOMETRIC TERHADAP PENINGKATAN DAYA LEDAK TUNGKAI BAWAH PADA KOMUNITAS BOLA BASKET SAHABAT DI KOTA SAMARINDA: PLYOMETRIC EXERCISE ON INCREASING LOWER LIMB EXPLOSIVE POWER IN FRIENDS BASKETBALL COMMUNITY IN SAMARINDA CITY - DESY PERDANA; AHMAD AZRI GULAM (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
ABSTRACT Introduction: Decreased performance in basketball players can be caused by several factors, one of which is a decrease in the explosive function of the lower limbs which causes a decrease in skill in playing basketball. It can be increased again by doing some exercises, such as Polymetric Exercises . Purpose : to see the effect of plyometric training on increasing the explosive power of the lower limbs ball club . friendship basketball in the city of Samarinda. Method: Study desain is pre experimental one group pre test post test. The research was conducted on 15 altet samples . ball . basketball by providing plyometric exercises ( Front Box Jump , Lateral Bounds, Lateral Box Jump, Single Leg Deadlift to Jump, Single leg hops) and measuring explosive power using a vertical jump test . Results: The results of this study have a significant effect on increasing the explosive power of the lower limbs basketball athlete with mark significant p – value = 0.000 used paired sample t-test (p < 0.05). Conclusion: There is an effect of plyometric training on increasing the explosive power of the lower limbs of the friendship basketball community of Samarinda City.